2015
DOI: 10.1002/jssc.201501060
|View full text |Cite
|
Sign up to set email alerts
|

Simplifying and expanding the screening for peptides <2 kDa by direct urine injection, liquid chromatography, and ion mobility mass spectrometry

Abstract: The analysis of low-molecular-mass peptides in doping controls has become a mandatory aspect in sports drug testing and, thus, the number of samples that has to be tested for these analytes has been steadily increasing. Several peptides <2 kDa with performance-enhancing properties are covered by the list of prohibited substances of the World Anti-Doping Agency including Desmopressin, LH-RH, Buserelin, Triptorelin, Leuprolide, GHRP-1, GHRP-2, GHRP-3, GHRP-4, GHRP-5,GHRP-6, Alexamorelin, Ipamorelin, Hexarelin, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…In this study, intact GnRH and GnRH 7–10 were substantially degraded within a few days and undetected after 6 days' incubation at room temperature in canine urine. In equine urine, complete loss of GnRH was also observed within 7 days of storage at room temperature, [11] and in human urine GnRH is stable for 1 day at room temperature . Our results indicated that better analytes for detection of GnRH abuse are the metabolites GnRH 5–10, which was markedly degraded on incubation at room temperature but still detected after 6 days, and GnRH 6–10 which was relatively stable and it was also a stable degradation product of GnRH 5–10.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In this study, intact GnRH and GnRH 7–10 were substantially degraded within a few days and undetected after 6 days' incubation at room temperature in canine urine. In equine urine, complete loss of GnRH was also observed within 7 days of storage at room temperature, [11] and in human urine GnRH is stable for 1 day at room temperature . Our results indicated that better analytes for detection of GnRH abuse are the metabolites GnRH 5–10, which was markedly degraded on incubation at room temperature but still detected after 6 days, and GnRH 6–10 which was relatively stable and it was also a stable degradation product of GnRH 5–10.…”
Section: Discussionmentioning
confidence: 59%
“…A wide range of MS‐based methods for the detection of intact GnRH in urine have been reported including affinity isolation techniques based on antibodies or aptamers combined with nanoLC–MS or capillary electrophoresis‐mass spectrometry (CE‐MS), mixed‐mode solid‐phase extraction (SPE) followed by LC–MS and direct injection of urine into liquid chromatography‐ion mobility‐mass spectrometry (LC‐IM‐MS) . In vitro metabolites of GnRH were identified in human serum by LC–MS following SPE .…”
Section: Introductionmentioning
confidence: 99%
“…While the first analytical methods were based on sophisticated and laborious sample preparation procedures [1][2][3] [eg, solid-phase extraction (SPE)], more recent publications demonstrated the fitness-for-purpose of simplified approaches 4,5 (eg, dilute-and-inject approaches). While the first analytical methods were based on sophisticated and laborious sample preparation procedures [1][2][3] [eg, solid-phase extraction (SPE)], more recent publications demonstrated the fitness-for-purpose of simplified approaches 4,5 (eg, dilute-and-inject approaches).…”
Section: Introductionmentioning
confidence: 99%
“…A chromatographic system consisting of a 150 × 2.1 mm analytical column (particle size 5 μm) and operated with 0.2% formic acid (containing 1% DMSO, solvent A) and acetonitrile (containing 0.2% formic acid and 1% DMSO, solvent B) was connected via ESI to HRMS. Full scan and targeted selected ion monitoring (SIM) was conducted at a resolution of 70,000, and LODs between 0.1 and 1 ng/mL were accomplished for a total of 36 analytes, which was found competitive to earlier methods using, for example, online‐trapping LC–HRMS …”
Section: Peptide Hormones Growth Factors Related Substances and MImentioning
confidence: 99%